1987
DOI: 10.1017/s0022112087001800
|View full text |Cite
|
Sign up to set email alerts
|

Fast dynamo action in a steady flow

Abstract: The existence of fast dynamos caused by steady motion of an electrically conducting fluid is established by consideration of a two-dimensional spatially periodic flow: the velocity, which is independent of the vertical coordinate z, is finite and continuous everywhere but the vorticity is infinite at the X-type stagnation points. A mean-field model is developed using boundary-layer methods valid in the limit of large magnetic Reynolds number R. The magnetic field is confined to sheets, width of order R−½. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
115
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(122 citation statements)
references
References 14 publications
7
115
0
Order By: Relevance
“…This decay results from magnetic flux expulsion out of the rotating inner parts of each cell. By the way, in agreement with results of asymptotic studies (Soward, 1987) it was found that φ behaves like Rm −3/2 ⊥ and, therefore, α ⊥ like Rm…”
Section: Roberts Flowsupporting
confidence: 88%
“…This decay results from magnetic flux expulsion out of the rotating inner parts of each cell. By the way, in agreement with results of asymptotic studies (Soward, 1987) it was found that φ behaves like Rm −3/2 ⊥ and, therefore, α ⊥ like Rm…”
Section: Roberts Flowsupporting
confidence: 88%
“…Thus the solution 542 follows closely Childress (1979) and Soward (1987) and is detailed here for completeness…”
mentioning
confidence: 79%
“…and is determined by matching a non-trivial solution in the interior of the flow cells with problem for the whole of Regime I turns out to be identical to that arising in the ho-mogenisation approach and solved by Soward (1987). However, it is only in the limit Introducing the expansions…”
mentioning
confidence: 99%
“…Because the boundary layers occur along the streamlines, ψ(x, y) provides a good basis. We define ψ(x, y) as one coordinate and then define a family of lines orthogonal to the streamlines [Childress (1979); Soward (1987)] by φ(x, y) = C b · dl, where dl is the tangent to the streamlines. This is an "angle" variable that measures the distance along a given streamline.…”
Section: Asymptotic Basismentioning
confidence: 99%